Do Harvest Practices of Bromeliads and Forest Management in Sierra Norte of Oaxaca Have a Negative Effect on their Abundance and Phorophyte Preference? - Velazquez-Cardenas, Yetlanezi; Rendón-Aguilar, Beatriz; Espejo-Serna, Adolfo (Ethnobiology and Conservation, 2021)
The present study recorded inhabitants’ traditional knowledge and uses of bromeliads and the phorophytes present in their ecosystems in two localities of Oaxaca. We also evaluated the effect of harvest practices on the abundance and distribution of the populations of these epiphytes on different phorophytes, considering the existence, or not, of a Forest Management Program. Structured interviews were conducted with 60 adults to identify the species of bromeliads of greater cultural importance (BGCI). We identified recurrent harvest sites (RHS) and occasional harvest sites (OHS) in order to estimate the abundance and phorophyte preference of BGCI. Traditional names and uses of epiphytes and phorophytes are described; it was identified that Tillandsia deppeana, T. lucida and Catopsis occulta had the highest BGCI in both localities. Their populations showed greater abundance values in OHS in both localities compared with RHS (χ2 gl6 = 296.99, p < 0.05). T. deppeana and T. lucida were shown to prefer Quercus elliptica, while distribution of C. occulta showed a preference for Q. rugosa and Pinus oocarpa; however, phorophyte preference patterns of bromeliads may be influenced by the intensity of forest management. Decrease in abundance as the size category increased was recorded in three species, as well as the adult harvest. Finally, the inhabitants of both communities demonstrate similarities in their traditional knowledge, the intensity of harvest may be a factor influencing their abundance and preference of phorophytes, but also forest management programs determine the availability of bromeliads populations, due to the specificity phorophytes that some bromeliads exhibited.